Frontal Theta Dynamics during Response Conflict in Long-Term Mindfulness Meditators - Jo, Han-Gue; Malinowski, Peter; Schmidt, Stefan (Frontiers in Human Neuroscience, 2017)
Mindfulness meditators often show greater efficiency in resolving response conflicts than non-meditators. However, the neural mechanisms underlying the improved behavioral efficiency are unclear. Here, we investigated frontal theta dynamics - a neural mechanism involved in cognitive control processes - in long-term mindfulness meditators. The dynamics of EEG theta oscillations (4-8Hz) recorded over the medial frontal cortex (MFC) were examined in terms of their power (MFC theta power) and their functional connectivity with other brain areas (the MFC-centered theta network). Using a flanker-type paradigm, EEG data were obtained from twenty-two long-term mindfulness meditators and compared to those from twenty-three matched controls without meditation experience. Meditators showed more efficient cognitive control after conflicts, evidenced by fewer error responses irrespective of response timing. Furthermore, meditators exhibited enhanced conflict modulations of the MFC-centered theta network shortly before the response, in particular for the functional connection between the MFC and the motor cortex. In contrast, MFC theta power was comparable between groups. These results suggest that the higher behavioral efficiency after conflicts in mindfulness meditators could be a function of increased engagement to control the motor system in association with the MFC-centered theta network.